2014
DOI: 10.18608/jla.2014.13.17
|View full text |Cite
|
Sign up to set email alerts
|

eWorkbooks for Mathematics: Mapping the Independent Learning Experiences of Elementary Students with Learning Disabilities

Abstract: ABSTRACT:In this paper, we describe a small case study exploring how four elementary students with mathematics learning disabilities utilized mobile technology (the eWorkbook) during core math instruction in a general education setting. The lead author designed the eWorkbook intervention to provide a flexible learning experience optimized for diverse learners. Sophisticated video-coding software was used to map the actions of the students as they engaged with the tool during the independent practice portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The development of available technology can bring advantages of mathematics learning for students with learning disabilities (Hughes, 2019). Kaczorowski and Raimondi (2014) clarified the use of technology-assisted orientation in mathematics teaching and learning that can enhance understanding of mathematics and mathematical outcomes of students with learning disabilities. Previous studies have shown potential in using tablet devices and applications to facilitate the fulfillment of learning needs for students with learning disabilities (Hord et al, 2022).…”
Section: / 11mentioning
confidence: 99%
“…The development of available technology can bring advantages of mathematics learning for students with learning disabilities (Hughes, 2019). Kaczorowski and Raimondi (2014) clarified the use of technology-assisted orientation in mathematics teaching and learning that can enhance understanding of mathematics and mathematical outcomes of students with learning disabilities. Previous studies have shown potential in using tablet devices and applications to facilitate the fulfillment of learning needs for students with learning disabilities (Hord et al, 2022).…”
Section: / 11mentioning
confidence: 99%
“…Raca and Dillenbourg (2014) study how to extract and explore visual cues from video-recordings of an observational system for measuring classroom activity to provide teachers with additional information about students' level of attention as well as about their own energy and attention distribution in the classroom. Kaczorowski and Raimondi (2014) focuses on how to facilitate flexible learning optimized for diverse elementaryaged students learning mathematics, including students with learning disabilities. The authors argue that although state-of-the-art video-coding software is useful for studying engagement, independence, accuracy, and specific affordances and barriers to learning with mobile technology, the many-sided analysis of interviews, field notes, and video codes was necessary to come up with conclusions.…”
Section: Papers In the Special Sectionmentioning
confidence: 99%